Unveiling an 'invisible population': health, substance use, sexual behavior, culture, and discrimination among urban American Indian/Alaska Native adolescents in California. Issue 6 (18th August 2021) - D'Amico, Elizabeth J.; Dickerson, Daniel L.; Brown, Ryan A.; Klein, David J.; Agniel, Denis; Johnson, Carrie
ABSTRACT: Objectives: There are limited public health data on urban American Indian/Alaska Native (AI/AN) populations, particularly adolescents. The current study attempted to address gaps by providing descriptive information on experiences of urban AI/AN adolescents across northern, central, and southern California. Design: We describe demographics and several behavioral health and cultural domains, including: alcohol and other drug (AOD) use, risky sexual behavior, mental and physical health, discrimination experiences, involvement in traditional practices, and cultural pride and belonging. We recruited 185 urban AI/AN adolescents across northern, central, and southern California from 2014 to 2017 who completed a baseline survey as part of a randomized controlled intervention trial. Results: Average age was 15.6 years; 51% female; 59% of adolescents that indicated AI/AN descent also endorsed another race or ethnicity. Rates of AOD use in this urban AI/AN sample were similar to rates for Monitoring the Future. About one-third of adolescents reported ever having sexual intercourse, with 15% reporting using alcohol or drugs before sex. Most reported good mental and physical health. Most urban AI/AN adolescents participated in traditional practices, such as attending Pow Wows and learning their tribal history. Adolescents also reported discrimination experiences, including being a victim of racial slurs and discrimination by law enforcement. Conclusions: This study describes a select sample of California urban AI/AN adolescents across several behavioral health and cultural domains. Although these adolescents reported numerous discrimination experiences and other stressors, findings suggest that this sample of urban AI/AN teens may be particularly resilient with regard to behavioral health.